Analysis of Training Effectiveness and Training Methods Influence on Soft Skills and Performance in Public Works, Housing, and Settlement Area Offices of Sleman Regency - Rahmat Angga Wijaya; Arni Surwanti (Research Parks Publishers, 2022)
This study aims to analyze how training effectiveness affects soft skills, how training methods affect soft skills, how training effectiveness affects performance, how training methods affect performance, how soft skills affect performance, how soft skills mediate training effectiveness on performance, and how soft skills mediate the effect of training methods on performance. The research method used was quantitative research. The data collection technique was a questionnaire instrument with a Likert scale. The population of this study was all employees of the Department of Public Works, Housing, and Residential Areas of Sleman Regency. The sample was 275 respondents with the criteria of employees working more than 1 year. The method of data analysis used the analysis of Structural Equation Modeling or Structural Equation Modeling.